DIFFUSION OF HYDROGEN IN POROUS SILICON-BASED SENSORS - Dzhafarov, Tayyar; Yuksel, Sureyya Aydin (BEGELL HOUSE INC, 2010)
Porous silicon (PS) layers of 65% porosity on n-type (111) Si substrates were prepared by anodic etching. Au/PS/Si structures have been fabricated by evaporation of thin Au film onto the PS surface. Current-voltage characteristics and the open-circuit voltage (V(oc)) generation in Au/PS/Si structures were examined at different ambient humidities (water vapor) in the temperature range 295-365 K. Generation of a voltage from 10 to 400 m V with the increase of the relative humidity from 50% relative humidity (RH) to 95% RH was observed in Au/PS/Si sensors. The response and recovery time of open-circuit voltage generated in Au/PS/Si Schottky-type sensors under humid atmosphere depends on ambient temperature. The effective diffusion coefficient of hydrogen estimated from response (or recovery) V(oc) - t curves on placing (or removal) of Au/PS/Si sensors in (or out) of humid ambient (90% RH) in the temperature range 313-363 K increases from 3.1 x 10(-8) to 1.7 x 10(-7) cm(2)/s and is described as D = 9.2 x 10(-3) exp(-0.34 eV/kT). The possible mechanism of the hydrogen diffusion in porous silicon layers of Au/PS/Si sensors was considered.
Keywords: porous silicon; hydrogen diffusion; gas sensor; gold catalyst; INTERFACES; Thermodynamics; Engineering; Mechanics